2017
DOI: 10.3389/fncel.2017.00420
|View full text |Cite|
|
Sign up to set email alerts
|

HAX-1 Protects Glioblastoma Cells from Apoptosis through the Akt1 Pathway

Abstract: Glioblastoma is the most common malignant tumor in central nervous system (CNS), and it is still insurmountable and has a poor prognosis. The proliferation and survival mechanism of glioma cells needs to be explored further for the development of glioma treatment. Hematopoietic-substrate-1 associated protein X-1 (HAX-1) has been reported as an anti-apoptosis protein that plays an important role in several malignant tumors. However, the effect and mechanism of HAX-1 in glioblastomas remains unknown. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…By reviewing previous studies, we found that HAX-1 regulated cell growth and metastasis via JAK/STAT and Akt/mTOR signaling pathways. 23,24 In addition, JAK/STAT and Akt/mTOR are ubiquitously expressed, and their activation is also one of the factors causing malignant proliferation and metastasis of liver cancer cells. [25][26][27] The results of this study showed that silencing or overexpression of HAX-1 had no significant effect on the JAK/STAT pathway for SK-Hep1 and SUN387 cells.…”
Section: Discussionmentioning
confidence: 99%
“…By reviewing previous studies, we found that HAX-1 regulated cell growth and metastasis via JAK/STAT and Akt/mTOR signaling pathways. 23,24 In addition, JAK/STAT and Akt/mTOR are ubiquitously expressed, and their activation is also one of the factors causing malignant proliferation and metastasis of liver cancer cells. [25][26][27] The results of this study showed that silencing or overexpression of HAX-1 had no significant effect on the JAK/STAT pathway for SK-Hep1 and SUN387 cells.…”
Section: Discussionmentioning
confidence: 99%
“…FasL and Trail can bind to their receptors in turn causing caspase cascades and propagating the process of cellular apoptosis (Nagata, 1997; Vasaikar et al, 2015). The P53 protein regulates cellular apoptosis through multiple pathways, including activating the expression of pro-apoptotic genes and promoting the formation of apoptosome (Wawryk-Gawda et al, 2014; Deng et al, 2017). To identify genes incorporated in our model, we utilized qRT-PCR to define that Bim, P53, Trial, Bcl-2 and Mcl-1—but not FasL— as novel targets regulated by nuclear FOXO3 at the transcriptional level.…”
Section: Discussionmentioning
confidence: 99%
“…HAX1 suppresses NSCLC cell apoptosis through inhibiting AKT/mTOR signal pathway A recent study reported that HAX1 prevents glioblastoma cells from apoptosis through the Akt1 pathway, 15 and it has also been reported that the AKT/mTOR signal pathway plays an important role in NSCLC. AKT/mTOR signal pathway induces gefitinib-resistant of NSCLC.…”
Section: Silencing Of Hax1 Reduces Invasion and Epithelial-mesenchymamentioning
confidence: 99%
“…As a downstream of AKT, MDM2/p53 signal pathway has been reported to play an important role in glioblastoma cells and endothelial progenitor cells. 15 We further investigated whether the MDM2/p53 signal pathway participates in NSCLC cells transfected with si-HAX1. We observed the protein level of p-MDM2 was reduced and p53 was increased in A549 and H1299 cells after si-HAX1 transfection (Fig 5a,b).…”
Section: Silencing Of Hax1 Reduces Invasion and Epithelial-mesenchymamentioning
confidence: 99%